2017
DOI: 10.1038/s41698-017-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

ALK G1269A mutation as a potential mechanism of acquired resistance to crizotinib in an ALK-rearranged inflammatory myofibroblastic tumor

Abstract: Inflammatory myofibroblastic tumors are rare mesenchymal neoplasms frequently harboring oncogenic chromosomal rearrangements, most commonly, involving the ALK (anaplastic lymphoma kinase) gene. Treatment of this molecularly defined subgroup with the anaplastic lymphoma kinase inhibitor crizotinib has shown to be effective. However, comparable to lung adenocarcinoma, resistance inevitably develops. Second generation anaplastic lymphoma kinase inhibitors such as ceritinib are able to overcome acquired resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…ALK inhibitors have shown remarkable effects against ALK-driven tumors. Several studies have shown that crizotinib exhibits impressive therapeutic effects in patients with ALK-translocated IMT [11,21]. These results support the dependence of ALK-rearranged tumors on ALK-mediated signaling and suggest a therapeutic option for genetically identified patients with the aggressive form of this soft-tissue tumor.…”
Section: Discussionsupporting
confidence: 54%
“…ALK inhibitors have shown remarkable effects against ALK-driven tumors. Several studies have shown that crizotinib exhibits impressive therapeutic effects in patients with ALK-translocated IMT [11,21]. These results support the dependence of ALK-rearranged tumors on ALK-mediated signaling and suggest a therapeutic option for genetically identified patients with the aggressive form of this soft-tissue tumor.…”
Section: Discussionsupporting
confidence: 54%
“…The gene fusion event confers constitutive activation of ALK and treatment with crizotinib inhibited constitutive phosphorylation of ALK and activation of downstream PI3K and MAPK signaling cascades. 38 Recently, Michels et al 42 has demonstrated that an ALK p.G1269A mutation was detected in a patient with DCTN1-ALK fusion who developed acquired resistance to crizotinib. Unfortunately, we were unable to obtain a repeat biopsy in our patient and therefore we could not confirm if any new mutations in ALK could have possibly contributed to the emergence of therapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, a report showed that ceritinib can overcome resistance to crizotinib caused by secondary mutations such as ALK G1296A. 22 After receiving ceritinib, patient 1 achieved PR. This case demonstrated L1196Q mutation can also be overcome by ceritinib.…”
Section: Discussionmentioning
confidence: 99%